A Systematic Review on Antituberculosis Drug Discovery and Antimycobacterial Potential of Biologically Synthesized Silver Nanoparticles: Overview and Future Perspectives. Issue 4 (1st December 2022) - Ezeh, Christian K.; Eze, Chibuzor N.; Dibua, Uju M. E.; Emencheta, Stephen C.
Abstract: Rapid emergence and quick evolution of drug-resistant and aggressive mycobacterial strains have resulted in the present antimycobacterial drug crisis and the persistence of tuberculosis as a major public health problem. Green/biological nanotechnologies constitute an interesting area of research for discovering antimycobacterial agents. This review focused on the biological (green) synthesis of silver nanoparticles (AgNPs) as an alternative source of antimycobacterial agents. Data for this study were searched and screened from three electronic databases (Google Scholar, PubMed and ScienceDirect) following the Preferred Reporting Items for Systematic Reviews and Meta-analyses flowchart. Data from in total 17 eligible studies were reported in this systematic review. Twelve of the 17 studies used plants to fabricate AgNPs, whereas the remaining five studies used microorganisms (bacteria and/or fungi). Silver as part of silver nitrate (AgNO3 ) was the metal precursor reported for the synthesis of AgNPs in these studies. Silver nanoparticles were mostly spherical, with sizes ranging from 12 to 140 nm. Results based on minimum inhibitory concentrations varied between studies and were divided into three groups: (i) those more effective than the antibiotic (controls), (ii) those more effective than plant extracts, and (iii) those less effective than the antibiotic controls. In addition, little or no cytotoxicity effects were reported. Silver nanoparticles were also shown to be highly specific or selective toward mycobacterial strains. This systematic review highlights the antimycobacterial potential of biologically synthesized AgNPs, underscoring the possibility of discovering/developing new antimycobacterial agents using biological synthesis approaches with less toxicity and high selectivity.